Comment (sa)voir ? Diana of the Crossways de George Meredith : la transparence paradoxale - Marina Poisson (Cahiers Victoriens et Edouardiens)
This article aims at exploring the paradoxical uses of transparency in Diana of the Crossways. In spite of claiming a diaphanous mode of existence, Diana displays evident signs of elusiveness, while the narrative, though seemingly transparent, proves opaque and misleading. Why? What are the hermeneutical, ethical and aesthetical implications of transparency? In a first movement, the article studies the moral quest for transparency as a natural virtue contrasting with the social vices of hypocrisy and opaqueness. The roles of nakedness and desire, reading and deciphering, are approached in this perspective. Transparency is then analysed as inherently paradoxical, both in stylistic and diegetic terms, as it proves artistic and artificial. In a last part, the violence of transparency is exposed through the social panopticon, which disrupts the initial dream of transparency while inviting us to challenge the Victorian categories of perception.